(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background and Objectives: Prostate adenocarcinoma is the most common malignancy in men worldwide and is characterized by significant heterogeneity in clinical behavior. Ki67, a nuclear proliferation antigen expressed during active cell-cycle phases, has emerged as a potential independent prognostic marker. This study aimed to evaluate Ki67 immunohistochemical expression and its association with clinicopathological parameters in prostate adenocarcinoma. Materials and Methods: A retrospective and prospective observational study was conducted over 18 months (July 2022–December 2023) at the Department of Pathology, Narayana Medical College and Hospital, Nellore, India. Sixty histologically confirmed prostate adenocarcinoma specimens (TURP chips, core needle biopsies, and radical prostatectomy specimens) were subjected to haematoxylin and eosin (H&E) staining and Ki67 immunohistochemistry. Ki67 expression was scored as 1+ (<10%), 2+ (10–50%), or 3+ (>50%) of stained tumour nuclei. Associations with age, PSA levels, Gleason grade group, tumour stage, metastasis, perineural invasion, PSA doubling time, and PSA response were analyzed using the chi-square test (SPSS v25.0). Results: Mean patient age was 58.03 ± 10.25 years (range 40–78). Ki67 expression was 1+ in 25%, 2+ in 45%, and 3+ in 30% of cases. Ki67 expression showed statistically significant associations with age (p < 0.001), PSA level (p = 0.020), Gleason grade group (p < 0.001), tumour stage (p = 0.007), metastasis (p = 0.037), perineural invasion (p = 0.004), PSA doubling time (p = 0.001), and PSA treatment response (p = 0.001). Notably, 77.8% of Grade 5 tumours and 83.3% of T4-stage tumours exhibited high Ki67 (3+) expression. Conclusion: Ki67 expression correlates significantly with multiple adverse clinicopathological parameters and treatment outcomes in prostate adenocarcinoma. It may serve as a valuable independent prognostic adjunct to Gleason grading and PSA, facilitating risk stratification and individualized management decisions.